Exploring the “Felitsa Cycle”: on Dmitry Khvostov’s panegyrical ode “To the Polish Felitsa” - Warda, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The article discusses the panegyrical ode “To the Polish Felitsa” by the 18th-century Russian poet Dmitry Khvostov, a work belonging to the so-called “Felitsa Cycle”. The first element of the cycle, both chronologically and in the sense of having initiated all subsequent compositions, is the ode “Felitsa” by the eminent Russian poet of the turn of the 19th century, Gavrila Derzhavin. Khvostov’s panegyric refers to specific historical events of the writer’s times, as well as to other authors’ poems in terms of poetics, imagery and means of expression. The figure of the empress Felitsa, in turn, echoes both her prototype from Catherine II’s fable and the heroine of Derzhavin’s abovementioned ode.